2010
DOI: 10.1128/cvi.00200-10
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Allergens Combined with Biological Markers in the Diagnosis of Allergic Bronchopulmonary Aspergillosis in Cystic Fibrosis Patients

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a frequent complication in cystic fibrosis patients. The diagnosis remains difficult and requires a combination of clinical, radiological, biological, and mycological criteria. The aim of this study was to analyze the added value of two recombinant antigens, rAspf4 and rAspf6, associated with the detection of specific IgG; precipitins; total IgE; and Aspergillus fumigatus in sputum for the diagnosis of ABPA. In a retrospective study, we determined the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
2
32
0
4
Order By: Relevance
“…Our study confirmed the high specificity (84.7%) of the IPD, based on in-house antigens that we have been using for Ͼ20 years, which was even greater (96.6%) when equivocal results were treated as negative (19). However, it was not significantly higher than that of the Bordier assay or the Bio-Rad assay, probably due to the loss of statistical power in the smaller sample size.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study confirmed the high specificity (84.7%) of the IPD, based on in-house antigens that we have been using for Ͼ20 years, which was even greater (96.6%) when equivocal results were treated as negative (19). However, it was not significantly higher than that of the Bordier assay or the Bio-Rad assay, probably due to the loss of statistical power in the smaller sample size.…”
Section: Discussionsupporting
confidence: 68%
“…This assay is novel in terms of its antigen composition, because it combines two recombinant antigens with somatic and metabolic antigens from A. fumigatus. We compared this assay with two other commercial EIAs, the Platelia Aspergillus IgG (Bio-Rad) and the ELISA classic Aspergillus IgG (Virion‫گ‬Serion), and an in-house IPD method (19).…”
mentioning
confidence: 99%
“…assumption arises from several lines of investigation. First, serological studies in patients with ABPA and SAFS demonstrate IgE responses to fungal products derived from in vivo germination of inhaled conidia into hyphae, as these antibodies exist as a response to fungal exoproducts, hyphal cell wall components expressed during growth phase and cytoplasmic antigens [21,22]. Secondly, there is mounting evidence that fungal hyphal products, including b-glucan and proteases, activate epithelial cells to secrete proinflammatory and Th2-polarising cytokines and chemokines directly via Toll-like receptor-induced signalling, via other innate sensors or via protease-activated receptors [23][24][25][26].…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 99%
“…ABPA is a severe complication related to A. fumigatus sensitisation and colonisation in the lung that affects patients with severe asthma (35,39,88,89). It is a frequent complication in cystic fi brosis patients (90). ABPA patients showed a marked increase in IgG and IgE antibodies against special A. fumigatus allergens (35).…”
Section: Health Effects Of Mouldsmentioning
confidence: 99%